2010
DOI: 10.5194/angeo-28-217-2010
|View full text |Cite
|
Sign up to set email alerts
|

Error analysis of Abel retrieved electron density profiles from radio occultation measurements

Abstract: Abstract. This letter reports for the first time the simulated error distribution of radio occultation (RO) electron density profiles (EDPs) from the Abel inversion in a systematic way. Occultation events observed by the COSMIC satellites are simulated during the spring equinox of 2008 by calculating the integrated total electron content (TEC) along the COS-MIC occultation paths with the "true" electron density from an empirical model. The retrieval errors are computed by comparing the retrieved EDPs with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
257
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(276 citation statements)
references
References 18 publications
19
257
0
Order By: Relevance
“…The COSMIC data have been broadly used for studying the ionospheric phenomena. Although the retrieval errors tend to increase closer to low latitudes and low altitudes [Yue et al, 2010], COSMIC electron density profiles in middle latitudes have shown a good agreement with ground observations [Lei et al, 2007]. The N m F 2 and h m F 2 derived from COSMIC profiles have also shown a good agreement with those derived from ionosonde measurements [Krankowski et al, 2011].…”
supporting
confidence: 68%
“…The COSMIC data have been broadly used for studying the ionospheric phenomena. Although the retrieval errors tend to increase closer to low latitudes and low altitudes [Yue et al, 2010], COSMIC electron density profiles in middle latitudes have shown a good agreement with ground observations [Lei et al, 2007]. The N m F 2 and h m F 2 derived from COSMIC profiles have also shown a good agreement with those derived from ionosonde measurements [Krankowski et al, 2011].…”
supporting
confidence: 68%
“…However, an extensive pre-processing and data screening was necessary for both the RO and ionosonde data to eliminate disturbances in the data and improve the data reliability. Many authors like Krankowski et al (2011), Hu et al (2014, Wu et al (2009), Yue et al (2010, and Lei et al (2007) evaluated the accuracy of electron density peaks, retrieved from F-3/C data, either on a regional scale by means of selected ionosonde stations allowing for a manual ionogram scaling or even used synthetic data to validate the accuracy under different conditions, e.g., under the influence of varying F10.7 indices. In this work, SPIDR network data based on automatically scaled measurements are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wu et al (2009) Lei et al (2007) evaluated correlations of maximum electron densities between F-3/C EDPs and ionosondes at the early stage of the constellation in July 2006. Krankowski et al (2011) validated F2 peak parameters of F-3/C measurements in the European sector during 2008 andYue et al (2010) studied the retrieval accuracy by means of synthetic data driven by background information of the NeQuick model to determine absolute and relative accuracies for NmF2 and hmF2.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with previous validation results comparing RO retrievals to ionosonde measurements. Comparison of COSMIC Ne profiles with NeQuick-derived profiles revealed good correlation; the standard deviation was ∼15% for NmF2 and ∼2% for hmF2 corresponded to global scale analysis (Yue et al 2010). There are several studies examining and estimating the accuracy of the retrieved COS-MIC Ne profiles by comparing them with globally distributed ionosonde data obtained from the National Geophysical Data Center (NGDC-NOAA) SPIDR (The Space Physics Interactive Data Resource) database (http://spidr.ngdc.noaa.gov/ spidr/).…”
Section: Comparison With European Ionosondes Data (Case-study)mentioning
confidence: 99%
“…The main source of inversion error is the spherical symmetry approximation. Yue et al (2010) compared COS-MIC Ne profiles with those obtained from the NeQuick empirical ionosphere electron density model. These simulations demonstrated that the Abel inversion method introduces significant errors in electron densities in the low-latitude region.…”
Section: Cosmic Datamentioning
confidence: 99%